The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1002/2013jc009165
|View full text |Cite
|
Sign up to set email alerts
|

A turbulent convection model with an observational context for a deep-sea hydrothermal plume in a time-variable cross flow

Abstract: [1] A turbulent convection model for a hydrothermal fluid discharging into a tidally modulated, stratified cross flow is used to investigate time-variable conditions in plumes, such as the one rising from Dante, a sulfide mound at $2175 m depth on the Endeavour segment of the Juan de Fuca Ridge. That plume is the consequence of the coalescence of 10 or more small, individual plumes from chimneys discharging hot, salt-diminished fluid into the near-bottom ocean. At Dante, the discharge encounters ambient horizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 53 publications
0
30
0
Order By: Relevance
“…Background flow affects the rise height of a hydrothermal plume insofar as stronger flow leads to plume bending and a reduced rise height [ Lavelle et al ., ; Tao et al ., ]. A time‐variable ocean current as observed at YK will therefore result in an equally variable rise height, and thus can account for the observed variability in the plume signals.…”
Section: Resultsmentioning
confidence: 99%
“…Background flow affects the rise height of a hydrothermal plume insofar as stronger flow leads to plume bending and a reduced rise height [ Lavelle et al ., ; Tao et al ., ]. A time‐variable ocean current as observed at YK will therefore result in an equally variable rise height, and thus can account for the observed variability in the plume signals.…”
Section: Resultsmentioning
confidence: 99%
“…Further, in a deep ocean seamount setting there are almost certainly lateral currents present that can also affect plume rise. To obtain a more sophisticated/less idealized estimate of the source heat flux at Teahitia, therefore, we have also conducted a 3-D numerical simulation using the plume model described in Lavelle et al (2013). The model is a 3-D non-hydrostatic, time-dependent, turbulent convection construct for a domain that is open to flow on all four sides.…”
Section: Oceanographic Evidence For Hydrothermal Perturbations At Teamentioning
confidence: 99%
“…FACETS | 2019 | 4: 183-209 | DOI: 10.1139/facets-2018-0027 202 facetsjournal.com 2012; Lavelle et al 2013;Bemis et al 2015), it seems likely that the laterally-spreading plume at Endeavour Ridge is consistently present. Although there are limited data available to detect tidal or seasonal changes, it has been found that particulate output from the main vent plumes at Endeavour Ridge can vary over an annual cycle by a factor of two (Dymond and Roth 1988;Kellogg 2011;Xu et al 2014).…”
Section: Burd and Thomsonmentioning
confidence: 99%